PENGARUH PEMBERIAN REWARD TERHADAP PRESTASI BELAJAR SISWA - NUR ALAM (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2023)
This research was motivated by the existence of a learning atmosphere that did not motivate students to study Civics and the lack of teacher appreciation for students resulted in these students considering rewarding as something normal and there are still some students who are remedial in learning. This resulted in low student learning outcomes. The average student learning outcomes are still much below the KKM, as seen in the odd semester exam scores for the 2021-2022 academic year. This study aims to determine how much the effect of giving rewards on student achievement in Civics subjects at Madrasa Aliya Bahrul Ulum Bontorea. This type of research is regression research with a quantitative approach. The population in this study were all students of Madrasa Aliya Bahrul Ulum Bontorea as many as 2 classes totaling 30 students. The sampling technique used is total sampling, which makes the entire population the subject of research when the population is less than 100 people, with a total sample of 30 people. Data collection in this study used a questionnaire, which was filled out by the respondents while the Bahasa Inggris learning outcomes were obtained from documentation techniques. The result of R Square is 0.305 or 30.5%. This shows the effect of giving rewards on student achievement is 30.5% in the low category with the remaining 69.5% explained by other variables not examined in this study. So it can be concluded that the effect of giving rewards on student achievement at Madrasa Aliya Bahrul Ulum Bontorea is 30.5%. So it can be said that Ha is accepted and Ho is rejected and there is a significant influence between giving rewards to student achievement at Madrasa Aliya Bahrul Ulum Bontorea. ABSTRAKPenelitian ini dilatarbelakangi oleh adanya suasana pembelajaran kurang memotivasi siswa untuk belajar Bahasa Inggris serta kurangnya penghargaan guru terhadap siswa mengakibatkan siswa tersebut menganggap pemberian reward sebagai sesuatu yang biasa-bisa saja dan masih ada sebagian siswa yang remedial dalam belajar. Hal tersebuat mengakibatkan rendahnya hasil belajar siswa. Rata-rata hasil belajar siswa yang masih banyak di bawah KKM, seperti yang terlihat pada nilai ujian tengah semester ganjil tahun ajaran 2021-2022. Penelitian ini bertujuan untuk mengetahui seberapa besar pengaruh pemberian reward terhadap prestasi belajar siswa pada mata pelajaran Bahasa Inggris di Madrasa Aliya Bahrul Ulum Bontorea. Jenis penelitian adalah penelitian regresi dengan pendekatan kuantitatif. Populasi dalam penelitian ini adalah seluruh siswa Madrasa Aliya Bahrul Ulum Bontorea sebanyak 2 kelas yang berjumlah 30 siswa. Teknik sampling yang digunakan adalah total sampling yaitu menjadikan seluruh populasi menjadi subjek penelitian ketika jumlah populasi kurang dari 100 orang, dengan jumlah sampel sebanyak 30 orang. Pengumpulan data pada penelitian ini menggunakan kuesioner, yang diisi oleh responden sedangkan hasil belajar Bahasa Inggris diperoleh dari teknik dokumentasi. Hasil R Square diperoleh sebesar 0,305 atau sebesar 30,5%. Hal ini menunjukkan pengaruh pemberian reward terhadap prestasi belajar siswa adalah sebesar 30,5% di kategori rendah dengan sisanya sebesar 69,5% dijelaskan oleh variabel lain yang tidak diteliti dalam penelitian ini. Jadi dapat disimpulkan besar pengaruh pemberian reward terhadap prestasi belajar siswa di Madrasa Aliya Bahrul Ulum Bontorea yaitu sebesar 30,5%. Maka dapat dikatakan Ha diterima dan Ho ditolak serta dapat pengaruh yang signifikan antara pemberian reward terhadap prestasi belajar siswa di Madrasa Aliya Bahrul Ulum Bontorea.